THE INFLUENCE OF GLOBALIZATION ON ENVIRONMENTAL LAW - Sarah Furqoni; Detania Sukaraja (LEX SOCIETAS: Journal of Law and Public Administration, 2024)
Globalization that creates adherence to values and norms between nations is a positive trend of globalization in various fields of life. Global environmental issues are a reflection of the international community on the environmental damage/pollution that has hit the world due to development. The type of legal research that the author uses in the preparation of this legal writing is normative juridical research type. The influence of globalization on environmental law, of course, will affect Indonesian legal politics in the environmental field. this can be seen from the government's policy of ratifying various international conventions relating to environmental protection. In addition to ratifying the various international conventions, the Indonesian government also issued several laws and regulations in the environmental field such as Law Number 32 of 2009 concerning Environmental Protection and Management. Existing environmental legal instruments should be enforced consistently, especially in environmental law enforcement related to carbon emissions that have an impact on environmental pollution by applying certification to factories that pollute the air.